Penguatan Strategi Bisnis Ukm Melalui Konsep Porter Sebagai Mitigasi Resesi Global - Sri Wulan Hastuti; Pristiyono Pristiyono; Abd. Halim (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
The implementation of Porter's strategy in the Micro, Small, and Medium Enterprises (MSMEs) business in Labuhanbatu Regency is classified as a crucial idea as well as a threat to businesses that are not serious about managing business strategies. Porter's strategy through low cost and differentiation is an important thing that needs to be considered by business actors. The purpose of this study is to prove and find out which MSMEs carry out the Porter implementation strategy for MSMEs in Indonesia and find out which factors of Porter's strategy are often used in MSME businesses. in strengthening MSMEs in Indonesia. The sampling technique refers to the minimum sample size in PLS-SEM, which is 30-100 sample sizes, so the authors set a sample size of 100 people. The sampling technique chose a purposive sampling technique and the data collection technique used a questionnaire (google form), interviews, and written or primary data. Each question in the online questionnaire has five alternative answer choices Strongly Agree, Agree, Disagree, Disagree, and Strongly Disagree. The author's data analysis technique uses SmartPLS 4.0. Based on the profiles of respondents, the types of Micro, Small, and Medium Enterprises (MSMEs) are dominated by fashion and culinary businesses. Based on the results of the description of the variables, it was concluded that respondents gave Agree and Strongly Agree responses for all the variables studied, and the results of research through testing the hypothesis there is a concordance where the low cost and differentiation variables significantly influence competitive advantage and competitive advantage affects consumer satisfaction.